Laying the BRICS of a new global order : from Yekaterinburg 2009 to Ethekwini 2013 - Bohler-Müller, Narnia; Kornegay, Francis A. (Africa Institute of South Africa, 2013)
The contributions in this compilation on the emergence of a new global order through BRICS serve to illustrate the complexities inherent in the creation of such a coalition - alternatively referred to as a 'grouping', 'association' or 'forum' - with each country differently situated geo-politically as well as ideologically and culturally, and in some instances even in conflict with one another in matters of regional peace and security. The fact that there are important commonalities of converging interests, amongst others, the status of emerging economic powers and the furtherance of South-South cooperation as well as reforming global governance, cannot and should not hide complexities and contradictions. These are clearly apparent both within and between the BRICS countries. These diversities are also clear from the varied perspectives of the chapter authors in this compilation, which is why we have assembled this collection relatively loosely as a means of expressing our intellectual and analytic convergences and divergences within and across BRICS. Each chapter contributor writes from a different discipline, country and regional perspective, and it is this diversity that enriches the debate and conversation. As such, there remains enormous room for debate on the subject matter of this book and the diverse contributions open up the parameters of the debate even further. The aim is to ensure that scholars, commentators and practitioners continue to engage critically with theory and practice related to global multilateralism, and BRICS in particular.